Money and Sustainability: Examining the Potential Moderating Role of Financial Capability and Decent Work on the Relationship between Income and Quality of life - Elliott, Amber (Organisational Psychology, 2022)
The inability of a large proportion of the working class to sustain a decent quality of life has placed increased importance on paying employees a living wage, that is, an income amount that enables meaningful participation in society above mere survival. However, while this notion seems promising, it does not account for the complexities in the relationship between income and quality of life; which, of course, is influenced by several moderating factors. This study considered two of these, financial capability and decent work, thereby assuming that the ability of income to effectively lead to a good quality of life is influenced by whether or not individuals engage in financial capability behaviours or perceive their work as decent. A cross sectional descriptive design was used and a final sample of N = 153 general salaried employees in South Africa participated in a self-report survey. Exploratory factor analysis revealed that each of the four financial capabilities (making ends meet, keeping track, planning ahead, and staying informed behaviours) were unidimensional in nature; while decent work produced a three-factor structure, inconsistent with its original five-factor conceptualisation. Spearman rho correlation results revealed that income was positively related to quality of life, and moderation analysis revealed that planning ahead was the only financial capability that influenced the relationship between income and quality of life. All other financial capabilities as well as decent work produced non-significant findings. Considering these results, study limitations and recommendations for future research are discussed, followed by outlining theoretical and practical implications.